2006
DOI: 10.1051/0004-6361:20065305
|View full text |Cite
|
Sign up to set email alerts
|

The X-ray binary 2S0114+650=LSI+65 010

Abstract: Context. The X-ray source 2S0114+650=LSI+65 010 is a binary system containing a B-type primary and a low mass companion believed to be a neutron star. The system has three reported periodicities: the orbital period, P orb ∼ 11.6 days, X-ray flaring with P flare ∼ 2.7 h and a "superorbital" X-ray periodicity P super = 30.7 days. Aims. The objective of this paper is to show that the puzzling periodicities in the system may be explained in the context of scenarios in which tidal interactions drive oscillations in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 22 publications
5
57
1
Order By: Relevance
“…In this approximation, the buoyancy force is not taken into account. Finally, we note that the results in this paper are obtained using a polytropic index n = 1.5, corresponding to a rigorous convective envelope, instead of n = 1 as was used previously (Moreno et al 2005;Koenigsberger et al 2006), although the difference between the results obtained for these two values of n is not significant. Moreno et al (2005) extended the model to include the computation of the photospheric absorption lines that would be produced by the perturbed stellar surface.…”
Section: Introductionmentioning
confidence: 90%
“…In this approximation, the buoyancy force is not taken into account. Finally, we note that the results in this paper are obtained using a polytropic index n = 1.5, corresponding to a rigorous convective envelope, instead of n = 1 as was used previously (Moreno et al 2005;Koenigsberger et al 2006), although the difference between the results obtained for these two values of n is not significant. Moreno et al (2005) extended the model to include the computation of the photospheric absorption lines that would be produced by the perturbed stellar surface.…”
Section: Introductionmentioning
confidence: 90%
“…These authors also found temporary quasi-periodic oscillations with a timescale of ∼2 h which they attribute to alternating high and low density regions within GP Vel's stellar wind. A similarly structured wind has been suggested to exist in the Be/X-ray binary system 2S0114+650 and to possibly be produced by tidally induced pulsations (Koenigsberger et al 2006). …”
Section: Dependence On Layer Depthmentioning
confidence: 97%
“…In the Milky Way, two very long period X-ray pulsars with periods >1000 s are known, both of them Be-HMXBs: SAX J2239.3+6116 at P = 1247 s (in't Zand et al 2001), SAX J0146.9+6121 at P = 1412 s (Hellier 1994). The longest X-ray period of all belongs to 2S0114+650 at P =10,008 s which has a B1 supergiant optical counterpart, although it is uncertain whether its X-ray period is the NS spin period or a periodic variation in the accretion rate, driven by tidal modulation of the stellar wind (Koenigsberger et al 2006). X-ray pulsars are the product of close-binary systems containing a pair of massive stars.…”
Section: Pulsars With Very Long Periodsmentioning
confidence: 99%